THE ROLE OF WORK-LIFE BALANCE AND HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE - Erwina, Erwina; Nurjannah, Nurjannah; Nurimansjah, Ris Akril; Amri, Amri (Jurnal Ekonomi Pembangunan STIE Muhammadiyah Palopo, 2024)
ABSTRACTIn the current era of globalization, competition in the business world is getting tighter, organizations are also required to keep up with the times that are increasingly changing in order to be able to compete and survive. The purpose of this study is to analyze the role of work-life balance and human resource development on employee performance. Research conducted at PT. Masmindo Dwi Area in Luwu Regency. The study was carried out for two months. This type of research is quantitative research. Data sources through primary data and secondary data. The main data collection technique in this study was through questionnaires distributed to employees at PT. Masmindo Dwi Area and through observation and interviews. The sample size was 75 employees. The data analysis technique used is to use SEM-PLS with the SMART PLS tool version 3. The results of the study found that work-life balance did not have a significant effect on employee performance. Human resource development does not have a significant effect on employee performance. While work life balanced has a significant effect on the development of human resources at PT. Masmindo Dwi Area in Luwu Regency. Keywords: Employee Performance; HR Development; Work Life BalanceABSTRAKDi era globalisasi saat ini, persaingan dalam dunia bisnis semakin ketat, organisasi juga dituntut untuk mengikuti perkembangan zaman yang semakin hari semakin berubah agar mampu bersaing dan bertahan. Tujuan dari penelitian ini adalah untuk menganalisis peran work-life balance dan pengembangan sumber daya manusia terhadap kinerja karyawan. Penelitian dilakukan di PT. Masmindo Dwi Area di Kabupaten Luwu. Penelitian dilakukan selama dua bulan. Jenis penelitian ini adalah penelitian kuantitatif. Sumber data melalui data primer dan data sekunder. Teknik pengumpulan data utama dalam penelitian ini adalah melalui kuesioner yang disebarkan kepada karyawan di PT. Masmindo Dwi Area dan melalui observasi dan wawancara. Jumlah sampel sebanyak 75 orang karyawan. Teknik analisis data yang digunakan adalah dengan menggunakan SEM-PLS dengan alat bantu SMART PLS versi 3. Hasil penelitian menemukan bahwa work-life balance tidak berpengaruh signifikan terhadap kinerja karyawan. Pengembangan sumber daya manusia tidak berpengaruh signifikan terhadap kinerja karyawan. Sedangkan work life balance berpengaruh signifikan terhadap pengembangan sumber daya manusia pada PT. Masmindo Dwi Area di Kabupaten Luwu. Kata kunci: Kinerja Karyawan; Pengembangan SDM; Keseimbangan Kehidupan Kerja